Study and Design of a 2.45-GHz Rectifier Achieving 91% Efficiency at 5-W Input Power - Wang, Ce; Yang, Bo; Shinohara, Naoki (IEEE microwave and wireless components letters, 2021)
To achieve a high-efficiency microwave wireless power transfer system, a high conversion efficiency rectifier is necessary. Brown (1974) designed rectifiers with approximately 3-W input power achieved 90% conversion efficiency for 2.45 GHz, and it maintains the record for maximum conversion efficiency. In this study, to design a high-efficiency and high-power rectifier, we designed a larger semiconductor metal junction area GaAs Schottky diodes possessing very low series resistance and high breakdown voltage. In addition, we built the SPICE model and package model for the diodes. The designed high conversion efficiency rectifier achieved 91% efficiency at 5-W input power for 2.45 GHz.